Food Security in South Africa : improving the availability, affordability, and quality of fresh produce in informal communities - De Beer, Darren (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2019)
Mini Dissertation (B Eng. (Industrial and Systems Engineering))--University of Pretoria, 2017.